Switchback deflections beyond the early parker solar probe encounters. Issue 1 (6th September 2022) - Laker, R; Horbury, T S; Matteini, L; Bale, S D; Stawarz, J E; Woodham, L D; Woolley, T
ABSTRACT: Switchbacks are Aflvénic fluctuations in the solar wind, which exhibit large rotations in the magnetic field direction. Observations from Parker Solar Probe's (PSP's) first two solar encounters have formed the basis for many of the described switchback properties and generation mechanisms. However, this early data may not be representative of the typical near-Sun solar wind, biasing our current understanding of these phenomena. One defining switchback property is the magnetic deflection direction. During the first solar encounter, this was primarily in the tangential direction for the longest switchbacks, which has since been discussed as evidence, and a testable prediction, of several switchback generation methods. In this study, we re-examine the deflection direction of switchbacks during the first eight PSP encounters to confirm the existence of a systematic deflection direction. We first identify switchbacks exceeding a threshold deflection in the magnetic field and confirm a previous finding that they are arc-polarized. In agreement with earlier results from PSP's first encounter, we find that groups of longer switchbacks tend to deflect in the same direction for several hours. However, in contrast to earlier studies, we find that there is no unique direction for these deflections, although several solar encounters showed a non-uniform distribution in deflection direction with a slight preference for the tangential direction. This result suggests a systematic magnetic configuration for switchback generation, which is consistent with interchange reconnection as a source mechanism, although this new evidence does not rule out other mechanisms, such as the expansion of wave modes.